Dicyclopentadithienothiophene (DCDTT)-based organic semiconductor assisted grain boundary passivation for highly efficient and stable perovskite solar cells. Issue 20 (4th May 2022) - Afraj, Shakil N.; Velusamy, Arulmozhi; Chen, Chung-Yu; Ni, Jen-Shyang; Ezhumalai, Yamuna; Pan, Chun-Huang; Chen, Kuan-Yu; Yau, Shueh-Lin; Liu, Cheng-Liang; Chiang, Chien-Hung; Wu, Chun-Guey; Chen, Ming-Chou
Abstract : New dicyclopentadithienothiophene (DCDTT ) based non-fullerene acceptors 1–3 are introduced into PSC films. The IN Cl -DCDTT −perovskite hybrid film exhibits an excellent power conversion efficiency of 21.39% . Abstract : The defects at the interface and grain boundaries of perovskite films downgrade the performance of perovskite solar cells (PSCs) dramatically. Hence, improving perovskite film quality is essential for the achievement of high-performance solar cells. Herein, three new dicyclopentadithienothiophene (DCDTT )-based non-fullerene acceptors (NFAs) IN-DCDTT (1 ), IN Cl -DCDTT (2 ), and IN Br -DCDTT (3 ) are developed as a promising platform for organic–inorganic hybrid perovskite solar cells to achieve simple preparation, high efficiency, and good stability. SEM and XRD data indicate that, with the addition of chlorinated NFA 2 in the active layer preparation, perovskite hybrid films exhibit larger grain sizes and higher crystallinity than pristine perovskite films. As shown by EDS and IR, all the non-fullerene acceptors (compounds 1–3 ) with functional carbonyl (CO) and cyano (CN) groups have good interaction with undercoordinated Pb atoms and passivate the trap states in the perovskite films. Time-resolved photoluminescence reveals that the molecule IN Cl -DCDTT (2 ) facilitates efficient hole extraction. Consequently, solar cells based on 2 −perovskite hybrid films yield an excellent power conversion efficiency of 21.39% with an FF of 0.82, a J sc of 23.71 mA cm −2, and a V oc of 1.10 V, which represents a significant improvement as compared to a PCE of 17% obtained for the control device. Meanwhile, devices based on IN-DCDTT (1 ) and IN Br -DCDTT (3 )−perovskite hybrid films also show enhanced performance with a slightly lower PCE of 19.21% and 20.59%, respectively than cells based on 2 −perovskite hybrid films. The cost-effective chlorinated IN Cl -DCDTT (2 ) and brominated IN Br -DCDTT (3 ) organic small molecules were successfully used as donor passivation agents to improve the photovoltaic performance of Pb-based PSCs. Furthermore, compound 1–3 derived PSC devices also exhibit excellent long-term stability enhancement. In particular, a device based on IN Cl -DCDTT (2 ) treated perovskite retains ∼90% of the initial PCE after 63 days in a glove box as compared to that (55%) of the control device. This simple surface treatment, by the addition of new NFAs, provides a new strategy to simultaneously passivate surface defects and enhance charge transport at the device interface.